Balancing Scattering Channels: A Panoscopic Approach toward Zero Temperature Coefficient of Resistance Using High‐Entropy Alloys. Issue 2 (8th November 2018) - Shafeie, Samrand; Guo, Sheng; Erhart, Paul; Hu, Qiang; Palmqvist, Anders
Abstract: Designing alloys with an accurate temperature‐independent electrical response over a wide temperature range, specifically a low temperature coefficient of resistance (TCR), remains a big challenge from a material design point of view. More than a century after their discovery, Constantan (Cu–Ni) and Manganin (Cu–Mn–Ni) alloys remain the top choice for strain gauge applications and high‐quality resistors up to 473–573 K. Here, an average TCR is demonstrated that is up to ≈800 times smaller in the temperature range 5–300 K and >800 times smaller than for any of these standard materials over a wide temperature range (5 K < T < 1200 K). This is achieved for selected compositions of Al x CoCrFeNi high‐entropy alloys (HEAs), for which a strong correlation of the ultralow TCR is established with the underlying microstructure and its local composition. The exceptionally low electron–phonon coupling expected in these HEAs is crucial for developing novel devices, e.g., hot‐electron detectors, high‐ Q resonant antennas, and materials in gravitational wave detectors. Abstract : In the high‐entropy alloy system Al x CoCrFeNi, x is used as a "knob" to elucidate the connection between composition, electrical resistivity, Kondo scattering, and microstructure. Furthermore, x controls the type of microstructure formed inside a spinodal region, which in turn tunes the temperature coefficient of resistance from positive to negative over a wide temperature range though different scattering mechanisms.